Cubes in a Triangle?

Geometry Level 3

B D BD is a cevian of equilateral A B C \triangle ABC such that A D 3 C D 3 = 25 ( A D C D ) AD^3 - CD^3 = 25(AD - CD) and A D C D AD \neq CD .

Find B D BD .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Nibedan Mukherjee
Feb 27, 2019

I hadn't heard of Stewart's theorem before, but it's very useful for this problem. Thanks for sharing!

David Vreken - 2 years, 3 months ago

Log in to reply

not mention sir! cheers..

nibedan mukherjee - 2 years, 3 months ago
David Vreken
Mar 3, 2019

Since the question implies that the equation holds for any A D C D AD \neq CD , consider the extreme case where C D = 0 CD = 0 .

Then A D 3 0 3 = 25 ( A D 0 ) AD^3 - 0^3 = 25(AD - 0) which solves to A D = 5 AD = 5 , and A D = A C = A B = B C = B D AD = AC = AB = BC = BD , so B D = 5 BD = \boxed{5} .

Chew-Seong Cheong
Feb 27, 2019

Let B D = x BD=x , the side length of A B C \triangle ABC be a a , A D = b AD=b , and C D = c CD=c . Then b + c = a b+c=a and

b 3 c 3 = 25 ( b c ) ( b d ) ( b 2 + b c + c 2 ) = 25 ( b c ) b 2 + b c + c 2 = 25 \begin{aligned} b^3-c^3 & = 25(b-c) \\ (b-d)(b^2 + bc + c^2) & = 25(b-c) \\ b^2 + bc + c^2 & = 25 \end{aligned}

Using cosine rule , we have:

{ B D 2 = A B 2 + A D 2 2 A B A D cos 6 0 x 2 = a 2 + b 2 a b . . . ( 1 ) B D 2 = B C 2 + C D 2 2 B C C D cos 6 0 x 2 = a 2 + c 2 a c . . . ( 2 ) \begin{cases} BD^2 = AB^2 + AD^2 - 2AB \cdot AD \cos 60^\circ & \implies x^2 = a^2 + b^2 - ab &...(1) \\ BD^2 = BC^2 + CD^2 - 2BC \cdot CD \cos 60^\circ & \implies x^2 = a^2 + c^2 - ac &...(2) \end{cases}

( 1 ) + ( 2 ) : 2 x 2 = 2 a 2 + b 2 + c 2 a ( b + c ) = 2 a 2 + b 2 + c 2 a 2 = a 2 + b 2 + c 2 = ( b + c ) 2 + b 2 + c 2 = b 2 + 2 b c + c 2 + b 2 + c 2 = 2 ( b 2 + b c + 2 c 2 ) x 2 = b 2 + b c + 2 c 2 = 25 x = 5 Since x > 0 \begin{aligned} (1)+(2): \quad 2x^2 & = 2a^2 + b^2 + c^2 - a(b+c) \\ & = 2a^2 + b^2 + c^2 - a^2 \\ & = a^2 + b^2 + c^2 \\ & = (b+c)^2 + b^2 + c^2 \\ & = b^2 + 2bc + c^2 + b^2 + c^2 \\ & = 2(b^2 + bc + 2c^2) \\ \implies x^2 & = b^2 + bc + 2c^2 = 25 \\ x & = \boxed 5 & \small \color{#3D99F6} \text{Since }x > 0 \end{aligned}

Nice solution!

David Vreken - 2 years, 3 months ago

Log in to reply

Glad that you like it.

Chew-Seong Cheong - 2 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...